2021
DOI: 10.3390/ijms22126590
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-R2/Caveolin-1 Pathway of Undifferentiated ARPE-19 Retina Cells: A Potential Target as Anti-VEGF-A Therapy in Wet AMD by Resvega, an Omega-3/Polyphenol Combination

Abstract: Age-related macular degeneration (AMD) is one of the main causes of deterioration in vision in adults aged 55 and older. In spite of therapies, the progression of the disease is often observed without reverse vision quality. In the present study, we explored whether, in undifferentiated ARPE-19 retinal cells, a disruption of the VEGF receptors (VEGF-R)/caveolin-1 (Cav-1)/protein kinases pathway could be a target for counteracting VEGF secretion. We highlight that Resvega®, a combination of omega-3 fatty acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…We have previously been able to show that RGA supplementation was able to decrease VEGF secretion in an in vivo mouse model [ 18 ]. In undifferentiated human ARPE-19 retinal cells mimicking the cells affected by AMD [ 24 ], this nutraceutical formulation was also able to reduce the secretion of VEGF by approximately 20% after 24 h of treatment, without affecting cell viability [ 22 ]. Firstly, in this same human retinal cell model that is widely used to test the efficacy of anti-angiogenic compounds, we tested whether the anti-angiogenic effect of RGA lasted over time, increased or, on the contrary, decreased.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously been able to show that RGA supplementation was able to decrease VEGF secretion in an in vivo mouse model [ 18 ]. In undifferentiated human ARPE-19 retinal cells mimicking the cells affected by AMD [ 24 ], this nutraceutical formulation was also able to reduce the secretion of VEGF by approximately 20% after 24 h of treatment, without affecting cell viability [ 22 ]. Firstly, in this same human retinal cell model that is widely used to test the efficacy of anti-angiogenic compounds, we tested whether the anti-angiogenic effect of RGA lasted over time, increased or, on the contrary, decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Once activated, it in turn triggers many intracellular signaling pathways. These include, in particular, the ERK1/2 pathway on which we have shown that RGA has an effect [ 22 ], but also other pathways, for instance the PI3K-AKT-mTOR pathway, which is crucial for cell survival, regulation of vasomotion and angiogenesis [ 27 , 28 ] In order to understand the impact of RGA on VEGF-A pathway through PI3K-AKT-mTOR, we investigated its effect on the expression of key proteins involved in the signaling cascade. Immunoblotting analysis revealed that RGA strongly decreases phosphorylation of c-RAF, in a concentration-dependent manner, as well as the protein expression of PI3K, AKT, mTOR and their respective phosphorylated forms ( Figure 2 A,B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we found that that IGF-1-induced Erk phosphorylation is significantly decreased in ARPE-19 cells in which Cav-1 has been depleted. Since it has been reported that the MAP Kinase pathways controls VEGF-A stimulated secretion in RPE cells [10,25,26], Cav-1 depletion may prevent IGF-1-induced VEGF-A secretion by attenuating the Erk kinase signaling.…”
Section: Discussionmentioning
confidence: 99%